Ketiadaan Asas Proporsionalitas dalam Perjanjian Bisnis antara Virtual Hotel Operator dengan Penyedia Hunian - Fahrezi, Natario Okta; Multazam, M. Tanzil (Web of Scientist International Scientific Research Journal, 2023)
This study raises the issue of whether the principle of proportionality in the business agreement between the VHO and Residential Provider has been fulfilled, using normative research and conceptual approach. Based on that, it was found that the agreement made was found to have not fully implemented the principle of proportionality, such as the minimal role of the residential provider in the process of determining the terms and conditions applicable in the agreement and the use of agreement made unilaterally and the use of some clause also contain things that either harm the residential provider. The conclusion obtained is that the application of the principle of proportionality so that it allows for an imbalance in the exchange of right and obligations that have the potential for parties to feel disadvantaged.